The New Epidemiology of Primary Biliary Cirrhosis - Griffiths, Laura; Dyson, Jessica K.; Jones, David E.J. (Seminars in Liver Disease, 2014)
Primary biliary cirrhosis (PBC) is an autoimmune cholestatic liver disease. Susceptibility to PBC probably arises from a combination of genetic and environmental factors. The prevalence of PBC varies both on an international and a regional level. This can be explained, in part, by differences in clinical practice and case-finding activity. It is likely, however, that substantive geographical differences exist both in terms of genetic susceptibility and environmental factors that potentially trigger the disease in genetically susceptible individuals. The study of the epidemiology of PBC has strongly supported the concept of an environmental triggering factor, but as yet no specific agent has been identified. Ongoing work to discover the environmental agent, as well as the mechanism that causes the disease will answer key questions as to the epidemiology of this complex autoimmune disease as well as providing useful information for other autoimmune conditions.
Keywords: primary biliary cirrhosis; epidemiology